2013
DOI: 10.1111/liv.12205
|View full text |Cite
|
Sign up to set email alerts
|

No difference in portal and hepatic venous bacterial DNA in patients with cirrhosis undergoing transjugular intrahepatic portosystemic shunt insertion

Abstract: No transhepatic gradient of bDNA was evident, suggesting that no major hepatic elimination of bDNA occurs in advanced liver disease. bDNA, in contrast to previous reports was largely unrelated to a panel of markers of inflammation and without relation to portal pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
1
25
1
2
Order By: Relevance
“…Intestinal bacterial translocation (BT) is part of this process and may be involved in activation of hepatic macrophages and thus development of cirrhosis and its complications. BT can be estimated by the circulating level of lipopolysaccharide (LPS)‐binding protein (LBP); however, a potential new marker of BT is the presence of bacterial DNA (bDNA) in the blood, which is associated with a poor prognosis in cirrhosis …”
Section: Introductionmentioning
confidence: 99%
“…Intestinal bacterial translocation (BT) is part of this process and may be involved in activation of hepatic macrophages and thus development of cirrhosis and its complications. BT can be estimated by the circulating level of lipopolysaccharide (LPS)‐binding protein (LBP); however, a potential new marker of BT is the presence of bacterial DNA (bDNA) in the blood, which is associated with a poor prognosis in cirrhosis …”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that no major hepatic elimination of bacterial DNA occurs in advanced liver diseases. Furthermore, the authors demonstrated that bacterial DNA was unrelated to a panel of markers of inflammation and without relation to portal pressure [42]. These divergent results underline the difficulty in investigating and better understanding the mechanisms and consequences of bacterial translocation in liver cirrhosis.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In this study, LPS-binding protein was measured by limulus amebocyte lysate assay [41]. In another study bacterial DNA was measured in blood from the hepatic vein and the portal vein during a TIPS procedure [42]. No transhepatic gradient of bacterial DNA was observed.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Additionally, it did not accurately predict the presence of SBP [44] . bDNA was also found to be largely unrelated to a panel of markers of inflammation and without association with portal pressure in patients with cirrhosis undergoing transjugular intrahepatic portosystemic shunt insertion [45] . No correlation between detection of bDNA in ascites and SBP was found [46] .…”
Section: Bacterial Dnamentioning
confidence: 98%
“…Rincón et al [39] , Sersté et al [40] , Feng et al [41] , Fujita et al [42] , Vlachogiannakos et al [43] , Mortensen et al [44] , Mortensen et al [45] , Appenrodt et al [46] LPS Gram (-) bacteria Pros: Correlation with TNF-α, stage of cirrhosis, prognostic value for severity of liver damage…”
Section: Bacterial Dnamentioning
confidence: 99%